Profit from Science - Danner, George. author. aut Link
XII, 236 p.
Keywords: In Profit From Science , author George Danner presents solutions to the big problems that modern business face solutions that are grounded in logic and empiricism. This book instructs business leaders in how to add the discipline and technical precision of the scientific method to their strategic planning and decision making.